The Aspects of Students' Gender and Ethnicity Representation of Conjugal Roles - O B Mikhailova; E A Kaminskaya (Peoples' Friendship University of Russia (RUDN University), 2011)
The article examines the contemporary representation of conjugal roles by Russian and Armenian students. It also reveals the specifics of differences and similarities in gender and ethnicity apprehension of the given ethnic groups' representatives and characterizes the tendency of alteration in conjugal roles representation.